2014
DOI: 10.1007/s00011-014-0783-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal study following burn injury in young rats is associated with skeletal muscle atrophy, inflammation and altered myogenic regulatory factors

Abstract: In conclusion, BI causes inflammation, atrophy and myogenesis stimulation in muscle as a result of systemic host response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…Regarding the downstream genes of NF-κB, including TNF-α, IL-1β and iNOS, our findings are consistent with previous studies that burn injury increases these pro-inflammatory genes in skeletal muscle [13, 25, 4447]. Previous studies have shown that TNF-α and IL-1β proteins are expressed in human and rodent skeletal muscle cells both under normal and disease conditions [4851] and that iNOS protein is induced in mouse skeletal muscle after LPS injection [52, 53] and burn injury [13].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the downstream genes of NF-κB, including TNF-α, IL-1β and iNOS, our findings are consistent with previous studies that burn injury increases these pro-inflammatory genes in skeletal muscle [13, 25, 4447]. Previous studies have shown that TNF-α and IL-1β proteins are expressed in human and rodent skeletal muscle cells both under normal and disease conditions [4851] and that iNOS protein is induced in mouse skeletal muscle after LPS injection [52, 53] and burn injury [13].…”
Section: Discussionsupporting
confidence: 92%
“…Upregulation of MyoD and myogenin together with an increase in inflammatory markers has also been reported in burn-induced muscle atrophy (53). Moreover, collagen-induced arthritis and immobilization increase muscle proteolysis and decrease muscle mass (15).…”
Section: Discussionmentioning
confidence: 96%
“…Myogenesis after burn is not compensatory to cell loss leading to atrophy (10). Myogenesis is dependent on muscle progenitor satellite cells.…”
Section: Introductionmentioning
confidence: 99%